ANALISIS TINGKAT BAGI HASIL DAN INFLASI TERHADAP DEPOSITO MUDHARABAH DI BANK SYARIAH INDONESIA - Yulissetyawati, Salma; Jauhariyah, Nur Anim; Syafa'at, Ahmad Munib (Universitas KH. MUkhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2025)
The purpose of this study is to analyze the effect of profit sharing rate and inflation on customer decisions in choosing mudharabah deposits at Bank Syariah Indonesia. This research methodology uses a quantitative approach with an explanatory research approach by analyzing the financial report data of Bank Syariah Indonesia using multiple linear regression tests. The results of the study indicate that the effect of the independent variable on the dependent variable partially is the profit sharing rate variable (X1) has a sig. value of 0.000 <0.05, then Ho is rejected and Ha is accepted, meaning that the profit sharing variable has an effect on mudharabah deposits. Then the inflation variable (X2) has a sig. value of 0.283> 0.05, then Ho is accepted and Ha is rejected, meaning that the inflation variable does not have an effect on mudharabah deposits. So it can be concluded that Profit Sharing has a positive and significant effect on Deposits while inflation has no effect on Deposits.